EFFECT OF POMELO (CITRUS GRANDIS) ETHANOLIC EXTRACT ON ATHEROSCLEROTIC PLAQUE FORMATION - Mudzakkir Taufiqurrahman; Kiky Martha Ariesaka; Hilda Khairinnisa; Wahyu Dian Puspita; Azka Darajat; Al Munawir (UNEJ e-Proceeding, 2016)
Cardiovascular disease is a major health problem in developed and developing countries and still be the first rank causing death in the world, including Indonesia. Most of cardiovascular disease caused by atherosclerosis. Macrophage apoptosis can reduce the size of atherogenic lesions and the progression of atherosclerotic plaque formation. Proapopstosis effects on macrophages owned by flavonoids. This study aims to know the potential of flavonoids found in Citrus grandis extract which works by suppressing the phosphorylation of AKT Ser473 so that the formation of foam cells (foam call) can be minimized. The research sample is 38 male Wistar rats weighing 90-150 grams. Samples were divided into 5 groups. All groups except normal control group were induced atherosclerosis by utilizing the shear stress mechanism at the branch of the abdominal aorta. Shear stress created by injecting adrenaline i.v. followed by hyperlipidemic diet (egg yolk) for 3 weeks. Then, during the next two weeks, the positive control group treated with simvastatin, while the treatment group were treated with extracts of C. grandis (ECG) known to contains flavonoids. Macroscopic showed that ECG could reduce atherosclerotic lesions. of citrus grandis. The sample data captured in the form of mouse blood and abdominal aortic tissues. Based on the results of the TLC screening, Ethanolic Extrxct Meanwhile, the group given simvastatin as a positive control also showed fewer atherosclerotic lesions. ECG proven to lower cholesterol and triglyceride levels of rats that had been induced atherosclerosis. Award ECG doses of 500 and 1000 mg/kg showed a significant decrease in cholesterol (p <0.01) compared to the negative control group. ECG is proven to reduce atherosclerotic lesions, so that ECG can be used as an adjuvant for simvastatin to achieve maximal therapeutic effect against atherosclerosis.